MODIFIKASI DAN UJI KINERJA MESIN PERAJANG DAUN TEMBAKAU GAYO - ., Irwansyah .; Hakim, Syahirman .; Kurniawan, Dedek . (Universitas Muhammadiyah Mataram, 2025)
In this study, the evaluation of the modification of the Gayo tobacco shredding machine was carried out with the aim of obtaining effective performance. Modifications were made by changing the cutting motion system with a 1 HP electric motor, a mechanical tobacco feeding system in the form of a conveyor, and a single blade. The results of the study succeeded in increasing the capacity of the shredding machine to 179.13 Kg/hour with a blade rotation speed of 450 RPM and a machine efficiency of 61.67%. The quality of the uniformity of the shredded Gayo tobacco was 3.03 mm and the percentage of uniformity of the shreds was 69.12%.